Long-term developmental effect of withholding parenteral nutrition in paediatric intensive care units: a 4-year follow-up of the PEPaNIC randomised controlled trial. (July 2020) - Jacobs, An; Dulfer, Karolijn; Eveleens, Renate D; Hordijk, José; Van Cleemput, Hanna; Verlinden, Ines; Wouters, Pieter J; Mebis, Liese; Guerra, Gonzalo Garcia; Joosten, Koen; Verbruggen, Sascha C; Güiza, Fabian; et al.
Summary: Background: The PEPaNIC randomised controlled trial, which recruited 1440 critically ill infants and children in 2012–15, showed that withholding parenteral nutrition for 1 week (late-parenteral nutrition), compared with early supplementation within 24 h of admission to the paediatric intensive care unit (early-parenteral nutrition), prevented infections, accelerated recovery, and improved neurocognitive development assessed 2 years later. Because several neurocognitive domains can only be thoroughly assessed from age 4 years onwards, we aimed to determine the effect of late-parenteral nutrition versus early-parenteral nutrition on physical, neurocognitive, and emotional and behavioural development 4 years after randomisation. Methods: This is a preplanned, blinded, 4-year follow-up study of participants included in the PEPaNIC trial (done at University Hospitals Leuven, Belgium; Erasmus Medical Centre Sophia Children's Hospital, Rotterdam, Netherlands; and Stollery Children's Hospital, Edmonton, AB, Canada) and of matched healthy children. Studied outcomes were anthropometrics; health status; parent-reported or caregiver-reported executive functions, and emotional and behavioural problems; and clinical tests for intelligence, visual-motor integration, alertness, motor coordination, and memory. Through multivariable linear and logistic regression analyses, after imputation for missing values (≤30%) and adjustment for risk factors, we investigated the effect of early-parenteral nutrition versus late-parenteral nutrition. This trial is registered with ClinicalTrials.gov, NCT01536275 . Findings: Between March 8, 2016, and Nov 8, 2019, 684 children from the original PEPaNIC trial (356 from the late-parenteral nutrition group and 328 from the early-parenteral nutrition group) were assessed for neurocognitive development at 4-years follow-up. Compared with the control group (369 healthy children), children who had critical illness had lower height (β-estimate −2·11 [95% CI −3·15 to −1·06]; p<0·0001) and head circumference (−0·42 [–0·67 to −0·18]; p=0.00077); and worse health status (eg, hospital admission odds ratio 4·27 [95% CI 3·12 to 5·84]; p<0·0001), neurocognitive (eg, parent-reported or caregiver-reported total executive functioning β-estimate 3·57 [95% CI 1·95 to 5·18], p<0·0001; total intelligence quotient −7·35 [–9·31 to −5·39], p<0·0001), and parent-reported or caregiver-reported emotional and behavioural developmental outcomes (internalising 2·73 [1·19 to 4·28], p=0·00055; externalising 1·63 [0·19 to 3·08], p=0·027; and total behavioural problems 2·95 [1·44 to 4·46], p=0·00013), adjusted for risk factors. Outcomes were never worse in the late-parenteral nutrition group compared with the early-parenteral nutrition group, but patients in the late-parenteral nutrition group had fewer parent-reported or caregiver-reported internalising (β-estimate −1·88 [95% CI −3·69 to −0·07]; p=0·042), externalising (−1·73 [–3·43 to −0·03]; p=0·046), and total emotional and behavioural problems (−2·44 [–4·22 to −0·67]; p=0·0070) than patients who had received early-parenteral nutrition, after adjusting for risk factors, and were no longer different from healthy controls for these outcomes. Interpretation: Omitting early parenteral nutrition use for critically ill children did not adversely affect long-term outcomes 4 years after randomisation and protected against emotional and behavioural problems, further supporting the deimplementation of early parenteral nutrition. Funding: European Research Council, Methusalem, Flanders Institute for Science and Technology, Research Foundation Flanders, Sophia Foundation, Stichting Agis Zorginnovatie, Erasmus Trustfonds, and the European Society for Clinical Nutrition and Metabolism.